Differences in penicillin-binding proteins of Streptococcus pyogenes and two derived, stabilized L forms. - Leon, O (1988)
The penicillin-binding proteins (PBPs) of Streptococcus pyogenes and two of its derived, stabilized (i.e., nonreverting) L forms, an osmotically fragile L form and a physiologic isotonic L form, were compared. The numbers of PBPs in the membranes of these organisms were 6, 4, and 2 for the coccus and the osmotically fragile and physiologic isotonic L forms, respectively. Likewise, the relative amounts of total PBPs were 1.00: 1.48:0.32 for this coccus and the osmotically fragile and physiologic isotonic L forms, respectively. The two largest PBPs (PBPs 1 and 2) of the coccus were absent in both L forms, while the smallest PBPs (PBPs 5 and 6) were found in all three membranes. Deacylation (half-life) of three of the four PBPs in the osmotically fragile L form membrane required a significantly longer time than did deacylation of these presumed identical enzymes in the parental coccal membrane. Conversely, there was no such difference between the only two PBPs of the physiologic isotonic L form and the same coccal membrane proteins. Intact cells of all three organisms secreted PBPs and what appeared to be penicilloic acid and a minimal amount of free penicillin. A greater amount of these PBPs was secreted by both L forms than by the coccus. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis patterns and ratios of secreted PBPs were identical to those from labeled membrane preparations. These differences are correlated with some of our previous findings and are discussed in terms of inhibition of cell wall synthesis and resulting membrane changes in these two derived, stabilized coccal L forms.